Risk factors of levodopa-induced dyskinesia in Parkinson's disease: results from the PPMI cohort. (December 2018) - Eusebi, Paolo; Romoli, Michele; Paoletti, Federico; Tambasco, Nicola; Calabresi, Paolo; Parnetti, Lucilla
Abstract Levodopa-induced dyskinesias (LID) negatively impact on the quality of life of patients with Parkinson's disease (PD). We assessed the risk factors for LID in a cohort of de-novo PD patients enrolled in the Parkinson's Progression Markers Initiative (PPMI). This retrospective cohort study included all PD patients enrolled in the PPMI cohort. Main outcome was the incidence rate of dyskinesia, defined as the first time the patient reported a non-zero score in the item "Time spent with dyskinesia" of the MDS-UPDRS part IV. Predictive value for LID development was assessed for clinical and demographical features, dopamine transporter imaging (DaTscan) pattern, cerebrospinal fluid (CSF) biomarkers (Aβ42, total tau, phosphorylated tau, total α synuclein) and genetic risk score for PD. Overall, data from 423 PD patients were analyzed. The cumulative incidence rate of LID was 27.4% (95% CI = 23.2–32.0%), with a mean onset time of 5.81 years from PD diagnosis. Multivariate Cox regression analysis showed several factors predicting LID development, including female gender (HR = 1.61, 95% CI = 1.05–2.47), being not completely functional independent as measured by the modified Schwab & England ADL scale (HR = 1.81, 95% CI = 0.98–3.38), higher MDS-UPDRS part III score (HR = 1.03, 95% CI = 1.00–1.05), postural instability gait disturbances or intermediate phenotypes (HR = 1.95, 95% CI = 1.28–2.96), higher DaTscan caudate asymmetry index (HR = 1.02, 95% CI = 1.00–1.03), higher polygenic genetic risk score (HR = 1.39, 95% CI = 1.08–1.78), and an anxiety trait (HR = 1.02, 95% CI = 1.00–1.04). In PD patients, cumulative levodopa exposure, female gender, severity of motor and functional impairment, non-tremor dominant clinical phenotype, genetic risk score, anxiety, and marked caudate asymmetric pattern at DaTscan at baseline represent independent risk factors for developing LID. Levodopa: Predicting side-effect risk Italian researchers identify seven independent risk factors for levodopa-induced dyskinesia in Parkinson's disease (PD) patients. Long-term treatment with levodopa can cause uncontrolled, involuntary movements which adversely affect patients' quality of life. Lucilla Parnetti and colleagues at the University of Perugia carried out a retrospective study of 423 patients enrolled in the Parkinson's Progression Markers Initiative to determine factors that are predictive of levodopa-induced dyskinesia at the time of diagnosis. They found that the risk of developing dyskinesia was greater in patients who were female, carried PD-associated mutations, presented higher disease severity at the time of diagnosis or neuropsychiatric symptoms in early PD. Taking these factors into consideration in the very early phase of PD could not only improve management of the disease, but also the design of future biomarker studies and clinical trials.